PERLINDUNGAN HUKUM TERHADAP HAK CIPTA LAGU YANG DIGUNAKAN TANPA IZIN DITINJAU DARI UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA DI PEKANBARU - Agrian Hilmar Alfattah; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The song is one of the works protected by copyright legislation, namely Act (UU) No. 28 of 2014 about copyright. But in practice there are often violations of Song or Music copyrighted works which are the property of a person or copyright holder, which is called art galleries are taken by the offender without the written consent of the copyright holder. Problems that arise now is how legal protection over the song. The protection provided to the song or music copyrighted works can be done in 2 ways. first, In a preventive way that is protection provided by the government with the aim to prevent the occurrence of violations. And second, Repressively in accordance with the objective to resolve the fold dispute by filing a lawsuit to the Commercial Court. This research includes types of sociological research, which is research by examining its legal aspects to look at legislation and comparing with the implementation on the ground gained by way of surveys. Analysis of the research material in this thesis using qualitative methods, in order to draw conclusions by using deductive methods. Then from the results showed that the entire creation works of song or music produced by Act (UU) No. 28 of 2014 about copyright, all concern parties can prove that his work is his creation, which can be proven by way of registering creations or in any way in accordance with the laws and regulations that govern it. And in the completion of the song is a lawsuit as compensation demands to the Court of Commerce and in the implementation of the rules of criminal law can be made by an authorized investigator, but most of the art galleries of resolving the problem of infringement of his work with the line of non litigation (other than the Court) or in a family.Key Words: Copyright protection - Song - Taking illegally